From audit-phobia to shared governance philosophies - Alpigiano, Carlotta; Baltos, Georgios (Qualitative and Quantitative Methods in Libraries; Vol 6 No 2 (2017): June 2017 Issue, 2019)
Libraries are rightfully recognised as the heart of academic institutions. However, they are not standalone, but interconnected with all other players within the same organisational universe: academia, administration, stakeholders, internal and external competitors and co-operators. Internal auditors‟ role is to promote quality standards along with a “continuous improvement” culture that includes efficiency, accountability and performance excellence at institutional level. Librarians have a long tradition of performance indicators‟ collection and evaluation. The crossroad where librarians and auditors meet each other is represented by an integrated methodology which links objectives, risks, performances and controls, harmonising them within the institutional context. The case of such a collaboration at European University Institute (EUI) is a noteworthy example.